The Impact of IFRS adoption and AQ upon Earnings Management in Saudi Stock Exchange (Tadawul) - Allehaidan, Maha Nasser (Journal of Economic, Administrative and Legal Sciences, 2020)
The main purpose of this paper is to examine the impact of International Financial Reporting Standards (IFRS) adoption and Audit Quality (AQ) on Earnings Management (EM) practices in Saudi Arabia listed firms. EM is measured by the discretionary accrual using Healy (1985) and Kothari, Leone, and Wasley (2005) models. The research sample contains 16 Saudi listed firms during the period from 2014 to 2019. Statistical analysis including t-test and linear regression were used to test the research hypotheses. The investigation indicates that there is a negative relationship between IFRS adoption and EM practices, especially if it is combined with AQ, while it found a positive relationship between firms’ size and accrual EM, and no significant impact of AQ on firms’ debt ratio and EM practices. The importance of these results lies in providing clear evidence that the adoption of IFRS in developing countries has helped reduce earnings manipulation practices, which contributes to gaining confidence in Saudi firms and thus attracting many foreign investments.
Keywords: International Financial Reporting Standards; Earnings Management; IFRS; Audit Quality; Saudi Stock Market Exchange